2012
DOI: 10.3390/s120912016
|View full text |Cite
|
Sign up to set email alerts
|

Grapefruit Fiber Filled with Silver Nanowires Surface Plasmon Resonance Sensor in Aqueous Environments

Abstract: A kind of surface plasmon resonance sensor based on grapefruit photonic crystal fiber (PCF) filled with different numbers of silver nanowires has been studied in this paper. The surface plasmon resonance modes and the sensing properties are investigated comprehensively using the finite element method (FEM). The simulation results show that the intensity sensitivity is related to nanowire numbers and the distance between two nanowires. The optimum value obtained is 2,400 nm/RIU, corresponding to a resolution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Different configurations (multi-hole, three-hole, "grapefruit", etc.) were proposed for plasmonic generation by coating the core or the other holes with NPs, over the last millimeters or centimeters of the fiber, or by filling some of the holes with metal [55][56][57][58][59][60][61][62]. In all cases, the guiding geometry must be such that some part of the guided light (usually the evanescent tail of guided modes) interacts with a metal surface along part of the length only (otherwise there would be too much loss and no light would reach the detector).…”
Section: Specialty Fibersmentioning
confidence: 99%
“…Different configurations (multi-hole, three-hole, "grapefruit", etc.) were proposed for plasmonic generation by coating the core or the other holes with NPs, over the last millimeters or centimeters of the fiber, or by filling some of the holes with metal [55][56][57][58][59][60][61][62]. In all cases, the guiding geometry must be such that some part of the guided light (usually the evanescent tail of guided modes) interacts with a metal surface along part of the length only (otherwise there would be too much loss and no light would reach the detector).…”
Section: Specialty Fibersmentioning
confidence: 99%
“…However, we should note that a larger volume ratio of chloroform will dilute the silver nanowires. As described in [24], the peak wavelength changes little but the peak loss decreases evidently when the number of silver nanowires in each air hole decreased. In other words, increase the volume ratio of chloroform will also decrease the peak loss.…”
Section: Theoretical Modelingmentioning
confidence: 80%
“…As shown in Fig. 1, some silver nanowires are embedded in the air holes of the first layer in numerical simulation and the distribution of silver nanowires refers to [23], [24]. Lu et al have demonstrated that when the number of silver nanowires embedded in each air hole of the first layer exceeds three, the sensor will get saturated wavelength and amplitude sensitivities.…”
Section: Introductionmentioning
confidence: 99%
“…Suppose that the light wavelength is λ , the analyte RI is na, the HF length is L , the function of core guided mode loss and wavelength is α(λ,na). The amplitude sensitivity is defined as [22]: S(RIU-1)=1α(λ,na)α(λ,na)na,…”
Section: Resultsmentioning
confidence: 99%